2015
DOI: 10.1038/sj.bdj.2015.293
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pilot oral health promotion programme 'Keep Smiling': perspectives from GDPs, health champions and school staff

Abstract: Community engagement and collaboration between health, education and the voluntary sector is feasible and integral in developing oral health promotion programmes aimed at children attending primary schools in a deprived area of London.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 4 publications
3
22
0
Order By: Relevance
“…Not getting consent would disrupt the implementation of POHP. This agrees with a study done in London where the authors revealed that some schools struggled with the return of consent forms, despite being rushed by the Dental Public Health (DPH) team [19].…”
Section: Discussionsupporting
confidence: 90%
“…Not getting consent would disrupt the implementation of POHP. This agrees with a study done in London where the authors revealed that some schools struggled with the return of consent forms, despite being rushed by the Dental Public Health (DPH) team [19].…”
Section: Discussionsupporting
confidence: 90%
“…However, some have indicated facing challenges for continuity of care and suggested strong recommendations for giving priority treatment appointments to school children at private clinics and Health Centers and suggested frequent dental check-ups at school. Similar parental views have resonated in another study also [25].…”
Section: Discussionsupporting
confidence: 77%
“…Children also influenced the parents who were initially reluctant in gaining positive consent when they saw their peers participating in the program and having a good experience with preventive treatment. Similar positive feedback for School Oral Health Programs has been obtained from parents in Australia, United Kingdom, and New Zealand [25][26][27][28].…”
Section: Discussionmentioning
confidence: 86%
“…There are challenges to working in schools, and these have been reported in other programmes which can limit success and sustainability due to time, space, and organization requirements. 9 , 10 We recognise some of these challenges and support the view that there is often an underestimation of the time (and resource) needed to engage and maintain a positive relationship with schools. Our community engagement “first” approach is designed to overcome these challenges by involving schools at the very start of the project cycle.…”
Section: Discussionmentioning
confidence: 74%